Premature ovarian failure: Immunological aspects and therapeutic strategies - Dragojević-Dikić Svetlana; Vasiljević Mladenko; Nikolić Branka; Pažin Vladimir; Tasić Lidija; Jurišić Aleksandar; Dikić Srđan; Perišić Živko (Vojnosanitetski Pregled)
nema